Secondary Electron Emission Yields from Fast Fluorine Ions on Copper and Amorphous Solid Water Foils - McLawhorn, Steven L. (East Carolina University, 2011)
The biological outcomes from charged particle radiation exposure are heavily influenced by the spatial patterns of energy distributed within the biological system. Monte Carlo track structure codes can be used to model these patterns of energy deposition event-by-event provided that cross sections for interactions are accurately known. Interaction cross sections in condensed phase materials cannot be directly measured and are therefore often estimated from theory. In order to test the accuracy of Monte Carlo electron transport codes double-differential electron emission yields, differential in energy and emission angle, have been measured from condensed phase targets following impact by fast Fluorine ions. Secondary electron emission spectra were measured using electron time-of-flight energy analysis for emission angles from 15° to 155° with respect to the incident beam. Copper foil targets were studied independently and later used as a substrate for amorphous solid water targets which best simulate the liquid water medium commonly used in track structure codes. The electron emission yields collected will serve in the future as a benchmark for comparison with simulated yields from Monte Carlo transport codes to assess the modeling accuracy of the production and transport of secondary electrons in condensed phase materials.
Keywords: Biophysics; Amorphous solid water; Electron yields; Heavy ion; Copper--Effect of radiation on; Fluorine; Electrons--Emission; Radiation